Implementing Sustainable Development on the Regional Level in Belarus - Aleksei Akhrymenka, Irina Sidorchuk; Alexei Grigoriev, Oksana Shmakova; Olga Kulai, Anton Parfenchyk (European Journal of Sustainable Development, 2017)
In accordance with the new agenda adopted by the General Assembly of the UN, methodological and practical approaches to sustainable regional development were prepared in the Republic of Belarus. They were developed during 2015-2016 in the context of international technical help project “The Support of Regional and Local Development in Belarus” financed by the European Union. The main goal is to promote consistent changes in the management of regional and local development based on the strategies for sustainable regional development. The mentioned approaches are a body of principles, methods, methodic, directions, which provide economic efficiency, social justice and ecological security on the republican, regional and local levels through consensus, coherence of interests and coordination of central and local governments, as well as population, business structures, civil society institutions. These approaches considered, there were developed six strategies for sustainable development in the regions of the Republic of Belarus. However, the absence of legal and institutional basis complicates the practical implementation of the mentioned findings. Additionally, the advantages of inclusive management and information technologies while providing public services are not accounted for fully. We suppose that during further planning of sustainable development specific attention should be paid to its key aspects, the specifics of the Belarusian legal system and the broad information campaign. It is relevant in Belarus to develop a set of measures to implement sustainable regional development strategies, which also include access to basic electronic public services to all the sections of the population. It is also important to note that European migration processes influence the Republic of Belarus, therefore for the purpose of promoting ordered, safe and legal mobility we should return to the question of developing multiple nationality institute. Keywords: sustainable development, digital public services, digital divide, multiple nationality, local government, Republic of Belarus